Iron fortification milk supplementation in reducing the incidence of low birth weight. - Tonny Sadjimin, Tonny Sadjimin (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1997)
The objective of the study was to examine the effectiveness of iron-fortification milk as a supplementation feeding for pregnant women in preventing the incidence of low birth weight. The design of the study was randomized controlled double-masked community trial. The setting were Maternity clinics at the health centers, private clinics, and hospital located in Yogyakarta Municipality, Indonesia. The patients were 138 pregnant women aged 20-30 years, parity of 2 or less, 24-26 gestation weeks, no adverse obstetric history or systemic diseases, signed informed consent. A well-trained field worker at least 24 hours after delivery measured the average weight and length of newborn. The low birth weight was considered to babies who have a birth weight of 2500 g. or less. A logistic regression was used to measure the effect of the intervention to the incidence of low birth weight controlled for several potential confounding variables. The demographic characteristics and laboratory indexes of mothers at the entry were equally distributed between both comparison groups. All 138 mothers were identified during the delivery, but some mothers were refused to have blood drawn at the time of delivery. The incidence of LBW in the study group was 1.4 % and in the control group it was 11.6%, the relative risk of 0.12 (95% CI 0.01 - 0.97). After controlling for potential confounding variable the relative risk become 0.32 (95% CI 0.11 - 0.98).Lactamil, the iron-fortification milks as the supplementation. protein-energy-micronutrient and vitamins to pregnant women are significantly prevent the incidence of low birth weight.Key words: iron - low birth weight - pregnant mother - fortification milk - birth length